Pathways of Disadvantage: Unpacking the Intergenerational Correlation in Welfare - Melisa Bubonya; Deborah A. Cobb-Clark (Institute of Labor Economics (IZA), 2020)
Our goal is to investigate the pathways that link welfare receipt across generations. We undertake a mediation analysis in which we not only calculate the intergenerational correlation in welfare, but also quantify the portion of that correlation that operates through key mechanisms. Our data come from administrative welfare records for young people (aged 23 – 26) and their parents over nearly two decades which have been linked to survey responses from young people at age 18. The mediators we consider jointly explain nearly a third (32.2 percent) of the intergenerational correlation in welfare participation and more than half (52.6 percent) of the link between parental welfare participation and young people's total welfare benefits. The primary mechanism linking welfare receipt across generations is the failure to complete high school. Adolescents in welfare-reliant families experience more disruptions in their schooling (e.g., school changes and residential mobility, expulsions and suspensions) and receive less financial support from their families both of which impact on their chances of completing high school and avoiding the welfare roll. Young people's risk-taking behavior (smoking, illicit drug use, delinquency and pregnancy) is also a key mechanism underpinning intergenerational welfare reliance. Physical and mental health, work-welfare attitudes and academic achievement, in contrast, have a more modest role in transmitting welfare receipt across generations.
Keywords: H53; I38; J62; 330; intergenerational welfare; social mobility; socioeconomic disadvantage; social assistance; welfare